Gestión y eficiencia en el gasto de funcionamiento universitario - Agustín García García; David de la Maya Retamar; Jesús M. García Iglesias (Colegio de Economistas de A Coru\~na, 2010)
– In this work we study the effect on the current expending of different models of managing the university budget, establishing different expenditure control policies, both in the way of managing and when introducing technological improvements. A panel data of expenditures in several basic resources for teaching and researching (electricity, telephony and water) is analysed, for a period with several changes in the model of managing. With the joint analysis of those data and the usual variables to quantify the university activity, we deduce what kind of management changes may improve the expenditure efficiency.
Keywords: H52; I22; 330; public expenditure efficiency; management; university administration